DESIGN OF E-ARCHIVE INFORMATION SYSTEMS OF INACTIVE RECORDS BASED ON MICROSOFT ACCESS AT HR DEPARTMENT DOCUMENT DIVISION PT KERETA API INDONESIA (PERSERO) DAOP 3 CIREBON - Fatimatu Zachra Adelia Putrie; Yayan Firmansyah (Records Management System Journal, 2022)
The Human Resources PT Kereta Api Indonesia (Persero) is a very crucial part of handling documents because it stores all employee and pension data archives, and oversees the Document Unit which manages all inactive archives from all work sections. Archives are the most important and basic thing that needs to be considered in all types of administrative and management activities in an organization because archives are information data stored about everything we do in our daily routine. However, the management of archives for the inactive archives of the HR still uses conventional archives where there is no archive backup in electronic form. This is classified as not effective and efficient if done in the present, and there is a risk of damage to the archive or loss of the archive due to forgetting to archive it. Judging from the archival situation for inactive archives that occurred here, the solution that was deemed appropriate was to design and create an electronic archive information system for inactive archives. This electronic archive uses Microsoft Access tools because its use is easy and quite familiar to use in offices that implement the Windows operating system.